Risk identification techniques for international contracting projects by construction professionals using factor analysis - Ullah S.; Xiaopeng D.; Anbar D.R.; Victor Amaechi C.; Kolawole Oyetunji A.; Ashraf M.W.; Siddiq M. (Ain Shams University, 2025)
Globally, managing political risk is an essential component of international contracting and project management. Due to political unpredictability and volatility in most nations, there could be a substantial influence on the successful completion of any construction project. To mitigate this, contractors employ a systematic strategy for risk management, including expropriation, civil disturbance, and shifts in governmental policies taking into consideration all the political risks connected to global projects. As a result of the political volatility, there is a need for political risk management (PRM) approaches by the International Construction Corporation (ICC). This study investigates the risk identification techniques for international contracting professionals in the construction sector. The methodology for conducting this investigation is based on data collection through questionnaires from construction sector professionals in both academia and industry. The tools were used to develop essential components from the factors established. This was then analysed using quantitative techniques to examine identified risk factors and make study deductions. The findings of this study identified the crucial PRM-related implications for global initiatives and various risks that were considered in typical construction projects. The political environment should be thoroughly examined, prospective risks should be noted, and risk-reduction tactics should be included in this plan. Thus, a successful project is achievable when contractors can identify the risks, preserve their investments, minimize project delays, handle disruptions, and boost project success rates. Additionally, political risks are invariably associated with construction projects, and this is considered a concern for foreign contractors. Thus, good identification techniques will ensure project preparedness, which is required by expatriates and foreign contractors. This is necessary as they need to ensure that their projects are successfully handled and that there are alternative plans to handle any unexpected event on the project. ? 2024 THE AUTHORS